The effect of Glomus intraradices on the physiological properties of Panax ginseng and on rhizospheric microbial diversity - Tian, Lei (J Ginseng Res, 2019)
BACKGROUND: Glomus intraradices is a species of arbuscular mycorrhizal fungi that, as an obligate endomycorrhiza, can form mutually beneficial associations with plants. Panax ginseng is a popular traditional Chinese medicine; however, problems associated with ginseng planting, such as pesticide residues, reduce the ginseng quality. METHODS: In this experiment, we studied the effect of inoculating G. intraradices on several physiological properties and microbial communities of ginseng. UV-Visible Spectrum method was used to detect physical properties. Denaturing gradient gel electrophoresis method was used to analyze microbial communities. RESULTS: The results indicated that inoculation with G. intraradices can improve the colonization rate of lateral ginseng roots, increase the levels of monomeric and total ginsenosides, and improve root activity as well as polyphenol oxidase and catalase activities. We also studied the bacterial and fungal communities in ginseng rhizospheric soil. In our study, G. intraradices inoculation improved the abundance and Shannon diversity of bacteria, whereas fungi showed a reciprocal effect. Furthermore, we found that G. intraradices inoculation might increase some beneficial bacterial species and decreased pathogenic fungi in rhizospheric soil of ginseng. CONCLUSION: Our results showed that G. intraradices can benefit ginseng planting which may have some instructive and practical significance for planting ginseng in farmland.